Responsible Management-as-Process of Smoothing–Striating: Transcending Freedom or Control Contingencies - Oliver Laasch; Christine McLean; Jeremy Aroles (Journal of Business Ethics, 2024)
Enactment of responsible management (RM) can be fostered by giving actors discretionary freedom to act responsibly and/or by controlling them to act responsibly. RM research has dominantly taken a contingency approach that focuses on conditions under which actors should choose either freedom or control. However, this approach does not offer insights into entangled freedom and control dynamics and is a poor fit for the inherently processual RM phenomenon. We propose a paradox process alternative, mobilizing the lens of smoothing–striating dynamics, which we apply to the Becoming Responsible Initiative (BRI) case. Smoothing fosters creativity, discretion, and lines of flight. It is dynamically entangled with striating, which fosters standardization, strictures, and the direction of enactment. We present a rhizomatic process model based on a thematic template analysis of 104 interviews, observations over 30 months, and documentary evidence. The model explains how a tension spring of over/under smoothing–striating drives RM enactment in four modes: pervasive smoothing, selective smoothing, rigid striating, and flexible striating. Each mode involves dynamics between smoothing–striating unfolding in distributed RM encounters. We contribute to the RM literature by presenting a framework explaining the paradoxical-processual dynamics of RM enactment. Our framework also transcends the freedom or control contingency approach, and adds an intricate methodology for processual analysis to the paradox discussion.
Keywords: 300; Responsible management; Freedom and control versus smoothing–striating; Paradox process